2019
DOI: 10.1177/1461444819858695
|View full text |Cite
|
Sign up to set email alerts
|

Metajournalistic discourse on the rise of gaming journalism

Abstract: Gaming journalism, which finds its origins in public relations-oriented gaming magazines, discursively attached itself to traditional journalism in the wake of the 2014 GamerGate controversy. Yet it had remained unclear where gaming journalism fits within the ecology of journalism. This study examines metajournalistic discourse regarding gaming journalism from 2010 to 2018 and analyzes 53 articles about gaming journalism from that period in order to understand how the broader journalistic field conceptualized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…Metajournalistic discourse refers to the “site in which actors publicly engage in processes of establishing definitions, setting boundaries, and rendering judgments about journalism’s legitimacy” ( Carlson, 2016 , p. 350). As journalism’s institutional conversation, metajournalistic discourse primarily involves journalists talking about journalism ( G. Perreault & Vos, 2020 ; Vos & G. Perreault, 2020 ). Some of this discourse is outward facing.…”
Section: Metajournalistic Discoursementioning
confidence: 99%
“…Metajournalistic discourse refers to the “site in which actors publicly engage in processes of establishing definitions, setting boundaries, and rendering judgments about journalism’s legitimacy” ( Carlson, 2016 , p. 350). As journalism’s institutional conversation, metajournalistic discourse primarily involves journalists talking about journalism ( G. Perreault & Vos, 2020 ; Vos & G. Perreault, 2020 ). Some of this discourse is outward facing.…”
Section: Metajournalistic Discoursementioning
confidence: 99%
“…Such discourse exists alongside and makes sense of news discourse by providing shared meanings about journalism as an epistemic practice. Such discourse can appear via news media outlets or in social media posts, trade journalists or, really, wherever journalists discuss journalism (Perreault and Vos 2020; Vos and Perreault 2020). Indeed, research has found that when it comes to writing about the “crisis” of journalism, journalists are the most dominant interpreters (Chyi et al, 2012).…”
Section: Journalism Labor In the Digital Eramentioning
confidence: 99%
“…Numerous role tensions exist within journalism, in particular between the roles of scrutinizing watchdog and advocate for specific people and causes (Hanitzsch & Vos, 2018). This tension is reflected in mobile (Perreault & Stanfield, 2019), political (Perreault et al, 2019) and gaming (Perreault & Vos, 2020) journalism, but is perhaps more acutely reflected in the context of sports journalists who have been questioned for confusing roles of enthusiast and journalist (Boyle, 2006).…”
Section: Literature Reviewmentioning
confidence: 99%